(untitled) (Intent Research Scientific Journal, 2023)
The article deals with topics like crypto assets, crypto market and crypto derivatives, their role in the economy development prospects. The authors emphasized that the crypto market is the most promising among all markets. It is noted that the crypto derivatives market is the fastest growing area in the modern economy. Brief information about the main terms of the sphere is given.